Epilepsy Occurrence and Circadian Rhythm: A Bibliometrics Study and Visualization Analysis via CiteSpace - Zhong, Dongling; Luo, Shanxia; Zheng, Linli; Zhang, Yonggang; Jin, Rongjiang (Frontiers in Neurology, 2020)
Objective: This study aimed to review the research status and to demonstrate the hot spots and frontiers of epilepsy and circadian rhythm via CiteSpace. Method: We searched Web of Science (WoS) for studies related to epilepsy and circadian rhythm from inception to 2020. CiteSpace was used to generate network maps about the collaborations between authors, countries, and institutions and reveal hot spots and frontiers of epilepsy and circadian rhythm. Results: A total of 704 studies related to epilepsy and circadian rhythm from the WoS were retrieved. Sanchez-Vazquez FJ was the most prolific author (17 articles). The USA and University of Murcia were the leading country and institution in this field with 219 and 22 publications, respectively. There were active collaborations among the authors, countries, and institutions. Hot topics focused on the interaction between epilepsy and circadian rhythm, as well as possible novel treatments. Conclusions: Based on the results of CiteSpace, the current study suggested active cooperation between authors, countries, and institutions. Major ongoing research trends include the circadian rhythm of epilepsy based on different epileptic focus and the interaction between epilepsy and circadian rhythm, especially through melatonin, sleep–wake cycles, and clock genes, which may implicate possible treatments (such as chronotherapy, neural stem cells transplantation) for epilepsy in the future.